Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.2139/ssrn.3253086
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Vector Autoregressions

Abstract: This article reviews Bayesian inference methods for Vector Autoregression models, commonly used priors for economic and financial variables, and applications to structural analysis and forecasting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 137 publications
0
4
0
Order By: Relevance
“…That is, for instance, the current disease status of a subject would be modeled using the disease status at previous time points. Reliable estimation of the model parameters can be challenging, especially with small datasets, 13 which is the case of the current study. Bayesian VAR models use prior information about model parameters 14 to help with the stabilization of the parameter estimation, a task that is sometimes difficult for classical VAR models.…”
Section: Methodsmentioning
confidence: 99%
“…That is, for instance, the current disease status of a subject would be modeled using the disease status at previous time points. Reliable estimation of the model parameters can be challenging, especially with small datasets, 13 which is the case of the current study. Bayesian VAR models use prior information about model parameters 14 to help with the stabilization of the parameter estimation, a task that is sometimes difficult for classical VAR models.…”
Section: Methodsmentioning
confidence: 99%
“…Kadiyala and Karlsson (1997) andMiranda-Agrippino and Ricco (2018) provide another example where asymmetric treatment of the endogenous variables in a VAR is appropriate and in line with prior beliefs: theory suggests that money neutrality implies that the money supply does not Granger-cause real output.ECB Working Paper Series No 2730 / September 2022…”
mentioning
confidence: 63%
“…Bayesian Vector Auto-regressions (VARs) are linear multivariate time-series models able to capture the joint dynamics of multiple time series (Miranda-Agrippin, S. and Ricco, G.; The earliest studies employing Bayesian VARs (BVARs) to macroeconomic forecasting are found in Letterman (1979) and Doan et al (1984) Since then, VARs and BVARs have been a standard macro-econometric tool routinely used by scholars and policy makers for structural analysis, forecasting and scenario analysis in an ever growing number of applications.…”
Section: Econometrics Analysismentioning
confidence: 99%